Kesenian Kuda Lumping Ditinjau Dari Perspektif Aqidah Islam Di Desa Pematang Ganjang Kecamatan Sei Rampah Kabupaten Serdang Bedagai - Shinta Wulan Dari (UIN Sumatera Utara, 2021)
This research is entitled Kuda Lumping Art from the Perspective of Islamic Aqeedah in Pematang Ganjang Village, Sei Rampah District, Serdang Bedagai Regency, because this Kuda Lumping art has deviated greatly from the purpose for which it was created. This Kuda Lumping art scene displays the attraction of trance, immunity, and magical powers or eating glass so that it can endanger the health of the player and for others. This can affect one's understanding of one's aqidah because the area of aqidah includes believing in the existence of the supernatural dimension. The hallmark of the magical element in this attraction is carrying out rituals using Islamic prayers and offerings to summon spirits to other than Allah which is a major sin. The people of Pematang Ganjang village still carry out Islamic law and still believe in magic. In essence, the art of Kuda Lumping in general has been attached and integrated into the community. It is a habit that has been passed down from one generation to the next. The methodology used in this research is through field research (Field Research) with a qualitative approach, data collection techniques are processed from direct observations by looking at village community activities, field interviews with only a few informants and documentation. The results of the study in Pematang Ganjang Village which focused on the art of Kuda Lumping in terms of the perspective of Islamic aqidah that 70% supported the existence of Kuda Lumping on the grounds of wanting to hold a harvest celebration event, on August 17 and more often found in weddings and circumcision as entertainment media. Every Muslim must have the correct aqidah and it is very important for players not to enter into the element of shirk if it is not fortified with a strong religion.